Mãe / Mulher atrás das grades: a realidade imposta pelo cárcere à família monoparental feminina - Silva, Amanda Daniele [UNESP] (2014)
The prison and its many aspects, mostly negative, affect directly the people who are housed there - the prisoners. However, as well as in society that is in a state of freedom, prison expresses the various inequalities between men and women, affecting these more intensely than those, exacerbating the precarious situation in which they serve their sentence. The female prison sets up with some peculiarities, among which we propose to study the changes occurring in the mono parental female family organization when the main responsible - the woman - is held. Unexpected situations of this nature require the mobilization of players outside the family to ensure the sustenance and protection of children and adolescents who are living away from their mothers, setting up, so, the network of family protection. However, it is frequent cases where the absence of that this network relegates the children of these prisoners to judicial actions, being put into court process that may result in institutionalization or adoption of them. Faced with this serious condition, we propose, using quantitative and qualitative research approaches, to identify the main changes occurred in mono parental female family due to imprisonment of the family responsible. Corroborating this view, we also try to emphasize the importance and the existence or not of a network of relationship or social protection for the care and maintenance of these prisoners‟ children that, with the mother's arrest, accentuate their degree of social vulnerability